Development of magnetic induction spectroscopy system in biomedical application to detect jaundice - Jurimah, A. J. (American Institute of Physics Inc., 2016)
Jaundice or hyperbilirubinaemia is a clinical problem that often occurs to new-born infants after birth. Normally, medical staffs uses heel puncture to examine bilirubin level by taking blood sample from the baby's heel. Unfortunately, this method might be risky to the baby because mistakes can cause osteomyelitis to the baby. Therefore, in order to overcome this issue, magnetic induction spectroscopy (MIS) is introduced to measure bilirubin level without taking any blood sample from the baby's heel. This system implements magnetic field to measure bilirubin level and its required transmitter coil and receiver coil to develop MIS system. Thereby, 2D model of MIS system is designed and COMSOL Multiphysics is used to simulate induced currents in biological tissue and resulting perturbation in magnetic field for different tissue properties in fingers layer. As a result, expected changes obtained when frequency value is increased and it shows that high frequency value have good current path when passes through biological tissue.